Métodos para la determinacion del plano oclusal - Laura-Cahuana, Jessica Gabriela (2021)
In oral rehabilitation, it is fundamental to accurately determine the orientation of the occlusal plane in patients with different occlusal alterations such as severe wear, partial and total edentulism and their consequences. It is important that the occlusal plane be as close as possible to the position occupied in natural dentition, since it mainly affects occlusal function, the masticatory muscles, the temporomandibular joint, phonetics and aesthetics. In addition, correct determination is the basis of treatment planning, as it is the aesthetic and functional reference plane, and determines the previous guide, mandibular movement patterns, masticatory efficiency and vertical dimension. Thus, the purpose of this study was to provide a review of the current scientific literature on the most commonly used and reliable methods for determining the occlusal plane. According to the literature, the occlusal plane should be located in the position occupied by the natural teeth, and its determination is made following a clinical sequence starting with the anterior sector at rest and while smiling, continuing with the posterior sector. There is no method of choice. However, individual analysis of each patient is important to determine the most adequate method. Methods including cephalometric and/or three-dimensional analysis provide greater precision for treatment planning.